Human Umbilical Cord Therapy Improves Long-Term Behavioral Outcomes Following Neonatal Hypoxic Ischemic Brain Injury - Penny, Tayla R.; Sutherland, Amy E.; Mihelakis, Jamie G.; Paton, Madison C. B.; Pham, Yen; Lee, Joohyung; Jones, Nicole M.; Jenkin, Graham; Fahey, Michael C.; Miller, Suzanne L.; McDonald, Courtney A. (Frontiers in Physiology, 2019)
Abstract Background: Hypoxic ischemic (HI) insult in term babies at labour or birth can cause long-term neurodevelopmental disorders, including cerebral palsy (CP). The current standard treatment for term infants with hypoxic ischemic encephalopathy (HIE) is hypothermia. Because hypothermia is only partially effective, novel therapies are required to improve outcomes further. Human umbilical cord blood cells (UCB) are a rich source of stem and progenitor cells making them a potential treatment for neonatal HI brain injury. Recent clinical trials have shown that UCB therapy is a safe and efficacious treatment for confirmed cerebral palsy. In this study, we assessed whether early administration of UCB to the neonate could improve long-term behavioural outcomes and promote brain repair following neonatal HI brain injury Methods: HI brain injury was induced in postnatal day (PND) 7 rat pups via permanent ligation of the left carotid artery, followed by a 90 min hypoxic challenge. UCB was administered intraperitoneally on PND 8. Behavioural tests, including negative geotaxis, forelimb preference and open field test, were performed on PND 14, 30 and 50, following brains were collected for assessment of neuropathology. Results: Neonatal HI resulted in decreased brain weight, cerebral tissue loss and apoptosis in the somatosensory cortex, as well as compromised behavioural outcomes. UCB administration following HI improved short and long-term behavioural outcomes but did not reduce long-term histological evidence of brain injury compared to HI alone. In addition, UCB following HI increased microglia activation in the somatosensory cortex compared to HI alone. Conclusion: Administration of a single dose of UCB cells 24 hours after HI injury improves behaviour, however a single dose of cells does not modulate pathological evidence of long-term brain injury.